2014
DOI: 10.1515/dmdi-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular functionality of CYP2C9 polymorphisms and their influence on drug therapy

Abstract: CYP2C9 metabolizes approximately 20% of clinically used drugs, including the narrow therapeutic window drugs warfarin and phenytoin. More than 16,000 variants have been reported in the National Center for Biotechnology Information CYP2C9 database, as well as 58 alleles in the official P450 Nomenclature Committee website. Two single nucleotide polymorphisms represented by the CYP2C9*2 and CYP2C9*3 alleles have been studied extensively. However, in addition to these two alleles, other genetic factors and an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Although in silico tools predict the probability of a harmful effect in genetic variations in protein function and structure, it is reported that in silico software may show inaccurate prediction in comparison with in vitro and clinical data [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Although in silico tools predict the probability of a harmful effect in genetic variations in protein function and structure, it is reported that in silico software may show inaccurate prediction in comparison with in vitro and clinical data [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to understand the effects of MDR1 polymorphisms on pharmacokinetics, no consensus has been reached on this issue because of the lack of a humanized animal model. Regarding the CYP2C family, the effects of CYP2C9 and CYP2C19 polymorphisms on metabolic activity toward drugs that are known substrates of these proteins have been reported 34 , 35 . Polymorphisms in UGT2 genes have also been reported to affect expression and metabolic activity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…). Published discrepancies in variant CYP2C9 activity are common and likely arise from variations in experimental procedures between laboratories (Jarrar and Lee ).…”
Section: Discussionmentioning
confidence: 99%
“…In silico analyses by Matimba et al (2009) significant correlation between the CYP2C9*9 allele and phenytoin metabolism was not detected in African epilepsy patients (Matimba et al 2009). Published discrepancies in variant CYP2C9 activity are common and likely arise from variations in experimental procedures between laboratories (Jarrar and Lee 2014).…”
mentioning
confidence: 99%